Facial nerve palsy: An atypical presentation of dengue fever - Mukherjee, Rishav; Debarup Das, (Asian Journal of Medical Sciences, 2023)
Dengue fever is a grave public health concern in tropical countries. The disease spectrum of dengue fever is multi-systemic, although neurologic complications of dengue fever is relatively uncommon. The pathogenesis of neurologic manifestations in dengue fever is not well understood and may be due to the neurotrophic effect of the virus, or related to the systemic effects of dengue infection, and immune mediated. Here in, we discuss the occurrence of isolated 7th cranial nerve lower motor neuron type palsy in a 23-year-old lady suffering from dengue fever. To date, there are very few case reports citing the involvement of facial nerve in dengue fever.